The future of citizen science: emerging technologies and shifting paradigms. Issue 6 (1st August 2012) - Newman, Greg; Wiggins, Andrea; Crall, Alycia; Graham, Eric; Newman, Sarah; Crowston, Kevin
Abstract : Citizen science creates a nexus between science and education that, when coupled with emerging technologies, expands the frontiers of ecological research and public engagement. Using representative technologies and other examples, we examine the future of citizen science in terms of its research processes, program and participant cultures, and scientific communities. Future citizen‐science projects will likely be influenced by sociocultural issues related to new technologies and will continue to face practical programmatic challenges. We foresee networked, open science and the use of online computer/video gaming as important tools to engage non‐traditional audiences, and offer recommendations to help prepare project managers for impending challenges. A more formalized citizen‐science enterprise, complete with networked organizations, associations, journals, and cyberinfrastructure, will advance scientific research, including ecology, and further public education.